(Post-)Kemalist Secularism in Turkey. Issue 1 (2nd January 2017) - Tombuş, H. Ertuğ; Aygenç, Berfu
Abstract: The relationship between the state and religion established by the founding Republican regime has often had discriminatory consequences for religious plurality in Turkey. From its foundation in 1923, the state maintained a model of secularism in which religious activities and facilities were brought under state control. The ruling Justice and Development Party (AKP) has challenged the so-called Kemalist secularism and claimed to offer a liberal alternative. However, the AKP's policies have also remained controversial. This article focuses on how and in what direction the AKP has transformed Kemalist secularism by examining institutional transformations in the military, the Presidency of Religious Affairs (Diyanet) and the national education system. It is argued that the AKP has maintained the same authoritarian practices and institutions in relation to religious plurality. In particular, the Diyanet and compulsory religious education have been appropriated by the AKP for the purpose of executing a conservative-Islamic political and social transformation that aims to eradicate plurality and create a monolithic society through indoctrination and a strict state monopoly over religious matters.